The role of forests in addressing global problems: what economic valuation methods won't tell us - Kaimowitz, D. (Tropenbos International, 2002)
Early forest valuation studies let many people to believe these methods would produce results that convinced policymakers of the economic value of forests. More recent studies suggest the only environmental service that forests provide with high economic value is carbon sequestration. Thus one is forced to conclude that either traditional economic methods do not provide an appropriate way of valuing forests or that timber and carbon are the only forest products and services that are really valuable. This paper supports the former view. It notes that: 1) forests provide important safety nets to power people, 2) good forest governance can reduce violent conflict, and 3) forests contribute many environmental services that we still do not fully understand.